Pengaruh Indeks Harga Konsumen Terhadap Tingkat Inflasi di Kota Ambon - Hanifah; Hamizar, Arizal; W Maruapey, Muammar; F Malawat, Fadli (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Inflation is one of the problems that is of concern to the government. One of the indicators used to assess the rate of inflation is the consumer price index. The aim of this research is to determine the effect of the consumer price index on inflation in the city of Ambon. The method used in the research is a quantitative approach using SPSS Statistics 27. The results of this research are that the consumer price index has a positive and insignificant effect on inflation. The consumer price index has an effect of 12.3% on inflation, while the rest is influenced by other variables not examined in this research.